2017
DOI: 10.4103/jcvjs.jcvjs_93_17
|View full text |Cite
|
Sign up to set email alerts
|

Functional and radiological outcomes of thoracolumbar traumatic spine fractures managed conservatively according to Thoracolumbar Injury Severity Score

Abstract: Aim:To study the functional and radiological outcomes in cases managed conservatively for single-level traumatic thoracolumbar spine fractures without neurological deficit.Materials and Methods:In this prospective study design, thirty patients who presented to tertiary care hospital and diagnosed with posttraumatic thoracolumbar vertebral fracture without any neurodeficit were recruited. All the patients were managed conservatively as per the protocol which included bed rest, spinal braces, and physiotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…and Bagga et al . [728] ODI, SF-36, and RMQ are similar to those reported in literature. [72728] Comparing our results with the current literature, we can appreciate that CRC has no inferior performances in clinical results than other conservative treatment protocols, but it is important to underline a better control of deformity in medium-long FU.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…and Bagga et al . [728] ODI, SF-36, and RMQ are similar to those reported in literature. [72728] Comparing our results with the current literature, we can appreciate that CRC has no inferior performances in clinical results than other conservative treatment protocols, but it is important to underline a better control of deformity in medium-long FU.…”
Section: Discussionsupporting
confidence: 85%
“…A lot of treatments were proposed for thoracolumbar fractures[567812181920] and the best treatment must be chosen taking in consideration: AO fractures classification, fracture dislocation, neurological status, patients' comorbidities, and compliance. There are several authors supporting conservative treatment with reduction, as well as those reporting excellent results with fracture reduction and stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change corresponds to 18.1 ± 10.4% of the initial height and was smaller than that of osteoporotic VCFs, which decreases by 21.8 ± 14.4% at 6 months. [ 5 ] Traumatic VCFs were reported to show 19.8 ± 7.4% height loss after 2 years, [ 8 ] and therefore about 90% of this height loss was assumed to be obtained during the first six months.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 – 7 ] Traumatic VCFs also showed the progression of vertebral collapse in studies involving long-time follow-up. [ 4 , 8 ] Six months after the onset is the minimum duration required before a disability certificate can be issued in several countries; [ 9 11 ] it is also the criterion for distinguishing short-term and long-term disability. [ 12 14 ] However, it was not reported that changes of traumatic VCFs in the first 6 months were significant enough to justify the waiting of six months for a disability certificate.…”
Section: Introductionmentioning
confidence: 99%